MODFLOW-Based Evaluation of Mine Drainage and Environmental Risks in the Kulon Progo Iron Sand Mining Area - Andrawina; Luliana; Venty Lestari (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2026)
This study investigates the hydrogeological characteristics and mine drainage challenges of the iron sand mining area along the southern coast of Kulon Progo, Special Region of Yogyakarta, Indonesia. The region is characterized by a shallow unconfined aquifer with high hydraulic conductivity (10?²–10?³ m/s), a groundwater table depth of only 0.5–3.0 m below ground surface, and close proximity to the Indian Ocean, all of which strongly influence mine drainage design and dewatering requirements. Hydrological analysis using the Gumbel Type I distribution estimated a 3-year return period rainfall of 153.30 mm/day with a rainfall intensity of 53.71 mm/h based on 10 years of rainfall data, although the relatively short dataset remains a limitation for extreme-value prediction accuracy. The required mine dewatering capacity was calculated at 55 m³/s with a 95% confidence interval of ±5.8 m³/s, including approximately 10 m³/s contributed by groundwater seepage. Dewatering operations pose several environmental risks, including groundwater table drawdown of 1.5–3.0 m, potential seawater intrusion, elevated total suspended solids (TSS) in runoff reaching 2.0 mg/L, and disruption of surrounding mangrove ecosystems. To support sustainable mining operations, this study recommends implementing targeted dewatering strategies supported by MODFLOW hydrogeological modeling, establishing real-time groundwater monitoring systems, conducting progressive reclamation, and ensuring compliance with Government Regulation No. 22/2021 concerning environmental quality standards.